Intralymphatic Administration of Adipose Mesenchymal Stem Cells Reduces the Severity of Collagen-Induced Experimental Arthritis - Mancheño-Corvo, Pablo; Lopez-Santalla, Mercedes; Menta, Ramon; DelaRosa, Olga; Mulero, Francisca; del Rio, Borja; Ramirez, Cristina; Büscher, Dirk; Bueren, Juan A.; Lopez-Belmonte, Juan; Dalemans, Wilfried; Garin, Marina I.; et al. (Frontiers in Immunology, 2017)
Mesenchymal stem cells (MSCs) are multipotent stromal cells with immunomodulatory properties. They have emerged as a very promising treatment for autoimmunity and inflammatory diseases such as rheumatoid arthritis. Previous studies have demonstrated that MSCs, administered systemically, migrate to lymphoid tissues associated to the inflammatory site where functional MSC-induced immune cells with a regulatory phenotype were increased mediating the immunomodulatory effects of MSCs. These results suggest that homing of MSCs to the lymphatic system plays an important role in the mechanism of action of MSCs in vivo. Thus, we hypothesized that direct intralymphatic (also referred as intranodal) administration of MSCs could be an alternative and effective route of administration for MSC-based therapy. Here, we report the feasibility and efficacy of the intralymphatic administration of human expanded adipose-derived mesenchymal stem cells (eASCs) in a mouse model of collagen-induced arthritis. Intralymphatic administration of eASCs attenuated the severity and progression of arthritis, reduced bone destruction and increased the levels of regulatory T cells (CD25+Foxp3+CD4+ cells) and Tr1 cells (IL10+CD4+), in spleen and draining lymph nodes. Taken together, these results indicate that intralymphatic administration of eASCs is very effective in modulating established collagen-induced arthritis and may represent an alternative treatment modality for cell therapy with eASCs.